OPTIMALISASI SUMBER DAYA MANUSIA MELALUI STRATEGI ARBITRASE PADA PT. BRI (PERSERO) TBK LAMPUNG - erlangga erlangga; Tina Miniawati Barusman (Universitas Bandar Lampung (UBL), 2025)
Unequal distribution and utilization of human resources (HR) can reduce banking efficiency and service quality. This study aims to analyze the current HR distribution in PT. BRI (Persero) Tbk Lampung, identify workload imbalances, and formulate arbitration strategies to improve productivity, efficiency, and organizational performance. A qualitative approach was applied using literature review, internal document analysis, and in-depth interviews. Findings reveal excess staff in urban units, staff shortages in rural units, a 35% competency mismatch, and disproportionate workloads. Implementing arbitration strategies through rotation, temporary assignments, and multi skilled workforce utilization proved to increase average productivity by 12%, improve workload distribution, and enhance customer satisfaction. In conclusion, arbitration strategy effectively optimizes HR and should be institutionalized by integrating workload analysis and competency mapping.